(3GdeSGQ GdGeQjcjs - (3LdGd(B, (3GdHfGs ((3GdGScfOQjI(B:s (3GdecJH GdYQHj GdMOjK(B,s, 2007)
(3GdQDi GdeSJbHdjI, GbJUGOjGJ GdHjFI, Mbhb GdedcjI, GdhaQGJ GdNGQLjI, GdeTGcd GdHjFjI, JfXje GdShb(B: (3eYdheGJ hYOe GdJCcO, JhLjg GdehGQO GdeSJfRaI, hGdehGQO GdeJLOOI, fXQI YGeI Ydi GbJUGOjGJ eQGbHI GdJdhjK, eQGbHI GdehQO GdKGHJ GdghGA GdeMGi, GdedhKGJ GdGbdjejI hGdYhdejI(B: (3GdeWQ GdMGeV hGdJYOjdGJ GdefGNjI, eQGbHI GdeUOQ GdeMehd dJdhjK GdghGA, eQGbHI JdhjK GdejGg, GdehGO GdSejI, SjGSI eQGbHI GdJdhK(B: (3JCKjQGJ JhRjYjIs
(3HHdjhZQGajG(B: (3U(B.275-285s
Keywords: (3GdGbJUGOs; (3GdHjFIs; (3GdejGgs; (3GdghGAs